Image-guided percutaneous ablation for lung malignancies - Shang, Youlan; Li, Ge; Zhang, Bin; Wu, Yuzhi; Chen, Yanjing; Li, Chang; Zhao, Wei; Liu, Jun (Frontiers in Oncology, 2022)
Image-guided percutaneous lung ablation has proven to be an alternative and effective strategy in the treatment of lung cancer and other lung malignancies. Radiofrequency ablation, microwave ablation, and cryoablation are widely used ablation modalities in clinical practice that can be performed along or combined with other treatment modalities. In this context, this article will review the application of different ablation strategies in lung malignancies.